Evaluation of the clinical effectiveness of diagnosis and monitoring of inflammatory and destructive diseases of the oral mucosa from the standpoint of a patient-guided approach - Yu. A. Makedonova; V. V. Shkarin; S. V. Dyachenko; L. M. Gavrikova; D. Yu. Dyachenko; L. V. Zhuravlev (Эндодонтия Today)
At present, a significant increase in inflammatory-destructive pathologies of the oral mucosa has been revealed. However, despite the high prevalence and the trend towards a constant increase in the number of diseases, there is no single diagnostic algorithm for examining and managing these patients in dental practice. To solve the above problems, a complex system of a patient-oriented approach to the diagnosis and monitoring of the inflammatory-destructive process in diseases of the oral mucosa was developed.Aim. To evaluate the effectiveness of the developed complex system of a patient-oriented approach to the diagnosis and monitoring of inflammatory-destructive diseases of the oral mucosa.Materials and methods. A survey of 60 patients with inflammatory-destructive diseases of the oral mucosa was carried out, which were divided into 2 groups. In the main group, diagnostics and monitoring were carried out using the developed system, in the control group – according to the generally accepted scheme.Results. Taking into account the data of the study, we can confidently speak about the clinical effectiveness of the developed complex system of a patient-oriented approach to the diagnosis and monitoring of the inflammatory-destructive process in diseases of the oral mucosa. When managing patients using the proposed system, a personalized approach is provided, the dynamics of the course of the pathological process is objectively and accurately assessed, certain periods of clinical observation are offered in order to correct the prescribed therapy regimen.Conclusions. The use of a patient-oriented approach in the diagnosis and monitoring of the system helps to reduce the time of regeneration of inflammatory-destructive diseases of the oral mucosa, improves the effectiveness of the treatment of this pathology, and also improves the patient's quality of life.